Involvement of a Primary Electrogenic Pump in the Mechanism for HCO(3)(−) Uptake by the Cyanobacterium Anabaena variabilis - Kaplan, Aaron (1982)
The response of the membrane potential to HCO(3)(−) supply has been studied in the cyanobacterium Anabaena variabilis strain M-3 under various conditions. Changes in potential were followed with the aid of the lipophilic cation tetraphenyl phosphonium bromide. Addition of HCO(3)(−) to CO(2)-depleted cells resulted in rapid hyperpolarization. The rate and extent of hyperpolarization were greater in low-CO(2)-adapted than in high-CO(2)-adapted cells. Addition of the electron acceptor p-nitrosodimethylaniline which resulted in O(2) evolution in CO(2)-depleted cells did not cause hyperpolarization. The hyperpolarization was not attributable to a change in pH or in ionic strength of the medium. Pretreatment with 3-(3,4-dichlorophenyl)-1,1-dimethylurea prevented the hyperpolarization. KCN depolarized hyperpolarized cells. Addition of HCO(3)(−) also brought about immediate K(+) influx which was succeeded after about 2 minutes by K(+) efflux. Two of the models considered would be capable of explaining these and previous findings: (a) a primary electrogenic pump for transporting HCO(3)(−) ions; (b) proton-HCO(3)(−) contransport, the driving force for which is generated by a proton pump which is sensitive to the HCO(3)(−) concentration.